DISTINCTIVE QUALITIES OF THE ARTISTIC LANGUAGE OF SERHIY HERASYMENKO - МАЗУР, В. П. (Art and Design, 2022)
Purpose: analyzing the distinctive qualities of the creative style of artist Serhiy Herasymenko in his paintings included in the ornamentation of the Stauropean Cossack Church of the Intercession of the Holy Virgin in Kyiv. Methodology. This research has been conducted using the historical and comparative methods, as well as the art critic approaches of figurative, stylistic and formal analysis. Results: The author offers the analysis of easel paintings created by the artist during 2004–2005, which now belong to the ornamentation of the Stauropean Cossack Church of the Intercession of the Holy Virgin in Kyiv. This paper focuses on specific works by S. Herasymenko, available at the time of the interview. In this article we’re covering the religious-themed creations of the artist. We’re also analyzing the artistic approaches Serhiy Herasymenko applies to creating religious-themed art. The focus here is on the artworks representing his unique artistic manner and showcasing the artist’s high potential. We’ve studied the stages of his artistic development, emphasizing on the input of mentors and colleagues who have influenced the evolution of his own unique manner. The article also covers S. Herasymenko’s own approach to interpretation of figure, composition and coloristic solutions in easel paintings. Scientific novelty: This essay is the first-ever introduction of the name of Serhiy Herasymenko, a modern Ukrainian artist, to academic discussion. The paper highlights distinctive figurative and stylistic qualities of his artistic language. The discussion features individual pieces of art from a private collection. This paper surveys an array of Herasymenko’s works with remarkable presentation of the artist’s constructive features of composition techniques, and his unique manner along with individuality. Practical significance: The study enabled the analysis of paintings of the modern Ukrainian artist Serhiy Herasymenko that he created while working on the ornamentation of the Stauropean Cossack Church of the Intercession of the Holy Virgin in Kyiv. The specific focus of this paper is on the composition, coloristic and stylistic distinctive features of Herasymenko’s artistic style; systemization of a specific layer of his artworks of that period. This may serve as a basis for further research and popularization of his art. The results of this paper will be beneficial for promoting Ukrainian culture in the global context.